Strategy and Marketing Communication of Islamic Educational Institutions - Holilur Rahman; Nur Atika Alias (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2024)
Competition in the world of education is one of the challenges for Islamic educational institutions in Indonesia. One solution to face these challenges is the existence of educational marketing activities in order to maintain the existence and increase the growth of educational institutions. The aim of this research is to describe the marketing strategy and communication process of educational institutions in promoting the excellence of their respective institutions. The research method used is a literature study using a descriptive approach to understand the concept of marketing strategy and communication for Islamic educational institutions. The research results show that when selecting a marketing strategy you can use a marketing mix strategy. In the marketing mix there are seven important elements, namely 7p: Product, Price, Place, Promotion, People, Physical Evidence and Process. Apart from that, you can also use a differentiation strategy. A differentiation strategy is a strategy that seeks a difference in educational institutions so that they can compete with other educational institutions. In implementing the differentiation strategy, there are several activities that can support the achievement of differentiation, namely unique academic programs, focus on certain fields, superior facilities and infrastructure, quality teachers, industry connections and job opportunities as well as an active learning approach. Components in marketing communications include several elements, namely source or communicator, message, media, recipient, effect and feedback.